(3HdhZ GdBQGH aj dWGFa GdYJGHs - (3eMeO Hf CMeO GdGfHGQj GdebQF, TeS GdOjfs ((3eMeO Hf YHO GdaJGM GdeZQHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi djS dg Chd jHOjg hdG BNQ jZfjI gPG cJGH LeYJg ef LhGgQ s
(3BNQgG (B:s
(3jhe GdbjGeg dCcKQ ef Ydi hLg GdGQV ef MLQ Je gPG GdcJGH s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B57 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(2589) s
Keywords: (3GdJGQjNs